The VIII International Symposium of Biomechanics and Medicine in Swimming, Jyvaskyla, Finland (1998)
More than 160 delegates from around the globe gathered at the University of Jyvaskyla for the VIII International Symposium of Biomechanics and Medicine in Swimming from June 28-July 2, 1998. Over 130 presentations in various formats (podium, poster, pool demonstration) were given at the symposium. We've chosen a few presentations to highlight in this conference report; among them, keynote addresses by David Costill and Mitsumasa Miyashita. First, Costill's presentation on training intensity and tapering. Intensity and Tapering Historical Perspectives Technique and Efficiency Training Load Model 3-D Techniques Altitude Drafting Swim Tests Training and Performance Estimating Hydrodynamic Forces Reducing Drag During Glides Flume Swimming